PEMBANGUNAN GEOPORTAL JARINGAN INFORMASI GEOSPASIAL DALAM MENUNJANG KETERSEDIAAN DATA DAN PENINGKATAN KINERJA SDM KABUPATEN GRESIK - Fauzan Roziqin; Fatimah Zahro; Adipandang Yudono (LPPM Universitas Terbuka, 2023)
In the management of the regional geospatial information network, evaluation needs to be carried out as a continuous improvement effort. The assessment focuses on both internal and external aspects in the process of geospatial information management. The purpose of this study is to determine the readiness of the development of the geoportal, the availability of data and human resources in Gresik District, as well as to identify the strengths and weaknesses. The method used in this research is descriptive analytic method, which identifies, evaluates, and assesses each instrument through data scanning and interviews. The results of this study show that the Gresik District Geospatial and Geodetic Network Node has achieved an